Does Media Coverage of Partisan Polarization Affect Political Attitudes?. (2nd April 2016) - Levendusky, Matthew; Malhotra, Neil
Abstract : The past decade has witnessed an explosion of interest in the partisan polarization of the American electorate. Scholarly investigation of this topic has coincided with the media's portrayal of a polity deeply divided along partisan lines. Yet little research so far has considered the consequences of the media's coverage of political polarization. We show that media coverage of polarization increases citizens' beliefs that the electorate is polarized. Furthermore, the media's depiction of a polarized electorate causes voters to moderate their own issue positions but increases their dislike of the opposing party. These empirical patterns are consistent with our theoretical argument that polarized exemplars in journalistic coverage serve as anti-cues to media consumers. Our findings have important implications for understanding current and future trends in political polarization.